Application of porous glasses in microfluidic devices - Evstrapov, A.A.; N.A. Esikova, N.A.; Rudnitskaja, G.E.; Antropova, T.V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Nowadays a perspective appears of applying porous glasses in microanalytical devices. The opportunity of application of porous glasses as optical sensors has been shown in the present paper. Preliminary results of studying the electroosmotic flows through porous glasses are discussed.
Optica Applicata, Vol. 38, 2008, nr 1, s. 31-38
Keywords: optyka; porous glasses; diffusion reflection spectroscopy; microfluidic; electrokinetic; electroosmosis